Enhanced thermal stability and oxidation resistance in La3-xTe4 by compositing metallic nickel particles. (1st February 2022) - Li, Jian; Liu, Ruiheng; Song, Qingfeng; Gao, Zhiqiang; Huang, Hui; Zhang, Qihao; Shi, Xun; Bai, Shengqiang; Chen, Lidong
Abstract: Lanthanum telluride (La3- x Te4 ) is one of the important candidates of thermoelectric (TE) materials working at high temperatures over 1000 K. However, the thermal stability and oxidation resistance of the TE materials become the crucial issue when they are working at so high temperatures. In this report, it is found that, although La3- x Te4 exhibits excellent thermal stability up to 1200 K under inert atmosphere, the existence of oxygen even in very low partial pressure causes serious oxidation and performance degradation at a temperature over 700 K. By introducing metallic nickel particles into La2.74 Te4 matrix forming La2.74 Te4 /Ni composites, the oxidation rate is greatly reduced both in air and low oxygen partial pressure (Po2  = 10 −3  MPa). The dense La2 NiO4 /Ni2 Te3 O8 /NiO oxide composite layer formed during oxidation is in charge of "blocking" the diffusion of oxygen. Dispersing Ni particles gives indistinct influence on the thermoelectric properties leading to a good dimensionless thermoelectric figure of merit as 1.0 at 1273 K in the La2.74 Te4 /10 vol.% Ni composite. Graphical abstract: Image, graphical abstract